Association of Necessity-Concerns Framework with medication adherence among Malaysian hemodialysis patients: A multicenter cross-sectional study - Soik Fun Lee, Chee Ping Chong (Journal of Applied Pharmaceutical Science, 2022)
This study aimed to assess the association between Malaysian hemodialysis patients’ Necessity-Concerns Framework and medication adherence. This was a cross-sectional multicenter study conducted in Penang, Malaysia, by purposive sampling. Data were collected using a 5-item Medication Adherence Report Scale (MARS-5) and the Beliefs about Medicine Questionnaire (BMQ). Multiple linear regression was used to assess the association between patients’ medication beliefs and adherence. A total of 325 hemodialysis patients were recruited from 8 hemodialysis centers. The mean age of patients was 60.18 ± 21.54 years, and they were prescribed a median of 9 (95% CI: 8.0–11.0) medications daily. The mean score of medication adherence was 23.41 ± 1.81 based on the MARS-5 score. In the BMQ analysis, 88.0% of the patients believed that their medications prevent them from becoming worse, while 36.3% expressed worry about the side effects. The Necessity-Concerns differential score was 5.26 ± 3.91, with 67.1% of the patients having an accepting attitude. The belief of getting very sick without medications was a significant predictor of medication adherence. Meanwhile, the worry about becoming heavily dependent on medications has a significant negative association with medication adherence. In conclusion, counseling should be customized for patients with negative beliefs about medications and potential nonadherence
Keywords: Medication beliefs, medication adherence, hemodialysis patients, Malaysia